Contribution of individual COPD assessment test (CAT) items to CAT total score and effects of pulmonary rehabilitation on CAT scores - Sarah Houben-Wilke; Daisy J. A. Janssen; Frits M. E. Franssen; Lowie E. G. W. Vanfleteren; Emiel F. M. Wouters; Martijn A. Spruit (Health and Quality of Life Outcomes, 2018)
Abstract Background The COPD Assessment Test (CAT) contains eight items (cough, phlegm, chest tightness, breathlessness, limited activities, confidence leaving home, sleeplessness and energy). The current study aimed 1) to better understand the impact of the respiratory and non-respiratory CAT item scores on the CAT total score; and 2) to determine the impact of pulmonary rehabilitation (PR) on CAT items and CAT total score. Methods CAT total score of ≥10 or ≥ 18 points was used to classify patients as highly symptomatic, a decrease of 2 points was considered as clinically relevant improvement. ‘Cough’, ‘phlegm’, ‘chest tightness’, ‘breathlessness’ were defined as respiratory items; ≥3 points on each item was defined as highly symptomatic. Results In total, 497 clinically stable patients (55% male, age 64.0 (57.5–71.0) years, FEV1 46.0 (32.0–63.0)% predicted, CAT total score 22.0 (17.5–26.0) points) were included. 95% had CAT score ≥ 10 points and 75% ≥18 points. Respectively, 45% and 54% of subjects scored high on 3 or 4 of the respiratory CAT items. Following PR, 220 patients (57.7%) reported an improved health status as assessed by CAT total score (− 3.0 (− 7.0–1.0) points). Change in CAT item scores ranged from 0.0 (− 1.0–0.0) to − 1.0 (− 2.0–0.0) points) with best improvements in ‘energy’ (− 1.0 (− 2.0–0.0)points). Conclusions A substantial number of patients classified as highly symptomatic did not report a high level of respiratory symptoms, indicating that non-respiratory symptoms impact on disease classification and treatment algorithm. The impact of PR on CAT item scores varied by individual item. Trial registration Netherlands National Trial Register (NTR3416). Registered 2 May 2012.